Effect of sulfur passivation and polyimide capping on InGaAs-InP PIN photodetectors. - Ravi, M.R (IEEE Transactions on electron devices)
It is shown in this work that sulfur passivation followed by a deionized water rinse reduces the dark current of InGaAs-InP PIN photodetectors significantly. This reduction in dark current is shown to be due to reduced recombination at the exposed mesa surface. Detectors with polyimide capping after sulfur passivation showed no degradation in characteristics with time.